Rancang Bangun Website Rekam Medis Elektronik di Fasilitas Pelayanan Kesehatan Praktik Dokter - Nurhayati; Yunita Wisda Tumarta Arif; Ahmad Yusron Yunizar (Universitas Duta Bangsa Surakarta, 2020)
Electronic medical records record electronic medical records which contain personal data, demographic data, social data, clinical / medical data. Processing of medical record documents at doctor's practice health facilities is still done manually, starting from patient registration, writing examination history, and storing medical record documents. One of the efforts to overcome these obstacles is by building an Electronic Medical Record website. The website development method uses the development life cycle system. Medical records are processed from input patient data, diagnostic data, action data, drug data, officer data, registration data, examination data. Then the data is processed to produce reports, including patient data, and examination data. The electronic medical record website used can simplify the processing of medical record data.